Microstructures and mechanical properties of a precipitation hardened refractory multi-principal element alloy. (December 2022) - Cui, Dingcong; Yang, Zhongsheng; Guo, Bojing; Liu, Linxiang; Wang, Zhijun; Li, Junjie; Wang, Jincheng; He, Feng
Abstract: Precipitation hardening is used as a powerful strengthening pathway to tailor the mechanical properties of traditional alloys. However, in refractory multi-principal element alloys (RMPEAs), the precipitates with remarkable strengthening effect are relatively less explored. Here, we report novel precipitation hardened body-centered-cubic (BCC) TiVNb RMPEAs through doping surplus boron. 2000 ppm (0.2 wt%) boron doping leads to TiB precipitates, which can enhance the yield strength of TiVNb by ∼350 MPa. Orowan strengthening caused by TiB precipitates serves as the primary strengthening mechanism compared to non-boron alloys. Due to boron doping, the dislocation-mediated deformation transfers from planar-slip to cross-slip and thus avoids stress concentration caused by high-density geometrically necessary dislocation. The excellent strengthening effect and tuned deformation mechanisms led to an optimal RMPEA with a yield tensile strength of ∼972 MPa and an elongation of ∼12%. This work demonstrates that TiB is an efficient precipitate in BCC RMPEAs, which is constructive for the development of precipitation hardened RMPEAs. Graphical abstract: Image 1 Highlights: Surplus boron doping is put forward to produce stable TiB precipitates in the TiVNb alloy. Nanoscale TiB precipitates can increase the yield tensile strength by 35.7% via Orowan strengthening. The cross slip in the TiVNbB RMPEA led to an undamaged elongation of ∼12%.